Fermentation of Carrot Juice Waste (Daucus carota L) with Probiotics and Utilization in Races of Chicken Layers on Egg Production and Quality - Nur Endang Sukarini (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2020)
The aim of this study was to test the use of carrot juice fermentation with probiotics in rations with different levels on the production performance and quality of egg-laying hens. The material used was Lohman Brown strain of laying hens, 27 weeks old with an average initial body weight of 1.69 kg, as many as 45 birds. The research was conducted with experimental methods and used a Complete Design Acal (CRD). The treatment tested was the use of Carrot Extract Fermentation (FLSW) with probiotic SOC in the feed consisting of T1 = 100% basal ration, T2 = basal ration (97.5%) + FLSW (2.5%): T3 = basal ration ( 95%) + FLSW (5%); T4 = basal ration (92.5%) + FLSW (7.5%); T5 = basal ration (90%) + FLSW (10%). The variables observed were production performance (consumption, egg production (HDA / Hen Day Average), egg weight, egg mass, feed conversion and income over feed cost) and egg quality variables (albumin index, yolk index, Haugh Unit (HU), yolk color, albumin pH, yolk pH). The results of the analysis of variance showed that the use of carrot extract fermentation (FLSW) with different levels had a significant effect on feed consumption (Sig.115) and HDA (Sig.063), yolk index value (Sig.087) and yolk color (Sig. 000). , and not significantly different on feed conversion (Sig. 403), albumin index value (Sig. 522), and Haugh Unit (Sig. 259). The conclusion of the research showed that the use of fermented carrot juice waste (FLSW) in the feed of laying hens had an effect on feed consumption, egg production (Hen Day Averag / HDA), yolk index and yolk brightness (yolk color), but had no effect on conversion. feed, Haugh unit and albumin index value. Key words : probiotics, fermentation, carrot juice waste, production performance, egg quality